Developing a world-class brand encompassing the holistic development process - Dharmasiriwardhana, A.; De Silva, N. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2020)
Developing countries are producing comparatively low numbers of world-class brands compared with developed countries. This is mainly due to the investment approach followed by organizations in developing countries. Most of these tend to invest in advertising and communication by following competition from established multinational brands in developing countries, where multinational brands heavily invest in consumer research, advertising and communication, and those brands have invested in their R&D and manufacturing core competencies in developed countries and divert the development to developing countries. As a result, firms in developing countries do not make the right investment in R&D, manufacturing, supply chain and market research core competency developments due to diversion of investment to advertising and communication to win competition and short-term profit. Link Natural Products (Pvt) Ltd is an exceptional, developing country case, involved in a 360º holistic approach to brand development process where the company has ensured investment in all important critical areas (R&D, manufacturing capabilities, market research, supply chain and distribution channels, development capabilities, advertising and communication) to develop the firm as a world-class personal care product manufacturer in the global market. The company directly invested and developed unique core competencies in R&D, manufacturing and inbound supply chain, while leveraging investments in market research, distribution channel development, advertising and communication through strategic alliances with capable organizations. Hence, based on its success story, we show that 360º holistic brand development with the right amount of investment in all the critical and important areas are important for becoming a world-class brand.
Keywords: World-class brand, 360º holistic approach, core competencies, developing countries, brand sustainability, Sri Lanka